2019
DOI: 10.1098/rsif.2019.0226
|View full text |Cite
|
Sign up to set email alerts
|

Collagen content and extracellular matrix cause cytoskeletal remodelling in pancreatic fibroblasts

Abstract: In many solid tumours a desmoplastic reaction takes place, which results in tumour tissue stiffening due to the extensive production of extracellular matrix (ECM) proteins, such as collagen, by stromal cells, mainly fibroblasts (FBs) and cancer-associated fibroblasts (CAFs). In this study, we investigated the effect of collagen stiffness on pancreatic FBs and CAFs, particularly on specific cytoskeleton properties and gene expression involved in tumour invasion. We found that cells become stiffer when they are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 62 publications
2
19
0
Order By: Relevance
“…It is expected though that the mechanical properties of the cell cortex in a spread and a suspended state vary, as the cortical thickness depends on cell spreading and is altered on de-adhesion of cells [ 72 ]. Recently, pancreatic CAFs were reported to exhibit a lowered elastic modulus compared with native fibroblasts from the pancreas, although similar changes in the stress fiber alignment as in our study were observed [ 73 , 74 ]. There are, however, some differences in the experimental setup.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It is expected though that the mechanical properties of the cell cortex in a spread and a suspended state vary, as the cortical thickness depends on cell spreading and is altered on de-adhesion of cells [ 72 ]. Recently, pancreatic CAFs were reported to exhibit a lowered elastic modulus compared with native fibroblasts from the pancreas, although similar changes in the stress fiber alignment as in our study were observed [ 73 , 74 ]. There are, however, some differences in the experimental setup.…”
Section: Discussionsupporting
confidence: 86%
“…In contrast, Sylianou et al. [ 73 , 74 ] probed non-confluent pancreatic fibroblasts that were immortalized. While organ-specific differences might not be excluded, we also detected patient-to-patient variability in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…We have selected fibroblast cells for the in vitro cytotoxicity studies because they are heterogeneous and dynamic cell lineage presenting with different populations between human tissues [18, 19]. Fibroblast cells can produce extracellular matrix and collagen, which play critical roles in wound healing [20]. Cancerous cells have been found more sensitive towards BPNSs exposure than normal cells, which is evident from cell viability assays.…”
Section: Discussionmentioning
confidence: 99%
“…Xie et al demonstrated a lower proliferative rate of human mesenchymal stem cells on collagen with stiff fibers than that with soft fibers [ 33 ]. In addition, Stylianou et al reported that an increase of collagen concentration elevated fiber density, stiffness, and contributed to an increase in cell spreading of fibroblasts [ 34 ]. In our study, we found the proliferation of HDFa was decreased by coating SCC at high concentrations, whereas the migration and invasion ability was increased, maybe due to the substrate stiffening.…”
Section: Discussionmentioning
confidence: 99%